2016
DOI: 10.1016/j.annepidem.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Racism in the form of micro aggressions and the risk of preterm birth among black women

Abstract: Purpose-This study sought to examine whether perceived interpersonal racism in the form of racial micro aggressions was associated with preterm birth (PTB) and whether the presence of depressive symptoms and perceived stress modified the association. Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 39 publications
0
91
0
Order By: Relevance
“…The primary objective of the study was to determine how racism is associated with PTD. 33 Self-identified African American women (≥18 years old) who delivered a singleton infant, were recruited at a hospital in Oakland County, Michigan. Women were excluded from the study if they: (1) did not speak English or (2) had intellectual disabilities, serious cognitive deficits, or significant mental illness, on the basis of history or any prior records.…”
Section: Methodsmentioning
confidence: 99%
“…The primary objective of the study was to determine how racism is associated with PTD. 33 Self-identified African American women (≥18 years old) who delivered a singleton infant, were recruited at a hospital in Oakland County, Michigan. Women were excluded from the study if they: (1) did not speak English or (2) had intellectual disabilities, serious cognitive deficits, or significant mental illness, on the basis of history or any prior records.…”
Section: Methodsmentioning
confidence: 99%
“…There is theoretical discourse, but limited direct evidence, linking the pathways and mechanisms for stress related to discrimination, racism or disrespect in healthcare to negative health outcomes such as PTB (Slaughter-Acey et al, 2016;Congdon et al, 2016;Geronimus et al, 2015). Given the consistency of the limited reports of its pervasiveness and profound potential impact, further research is urgently needed that incorporates the perspectives of women of color to address disrespect in health service delivery and reduce the perceived stress associated with pregnancy related care for all women.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that women of color experience longer lifetime exposure to chronic stress, which may lead to fluctuations in allostatic load (wear and tear) and contribute to the higher risk of PTB for these women (Braveman et al, 2015;Giurgescu et al, 2011). Other investigators have suggested that women of color experience discrimination, racism and disrespect in healthcare encounters and that this affects the health of women and their infants (Rankin et al, 2011;Tucker Edmonds et al, 2015;Ertel et al, 2012;Pullen et al, 2014;Nuru-Jeter et al, 2009;Dominguez et al, 2008;Slaughter-Acey et al, 2016). A recent study (SlaughterAcey et al, 2016) found significant associations between racial mircoaggressions and PTB in women who had mild to moderate, but not severe, depressive symptoms, but did not find a significant association between PTB and overall perceived stress.…”
Section: Background and Significancementioning
confidence: 99%
“…In addition, racial discrimination and experiences of interpersonal racism such as implicit racial bias and microaggressions during clinical encounters create disproportionate barriers to high‐quality, respectful, patient‐centered care experienced by Black people . Perinatal care, as currently designed and delivered in most settings in the United States, has proven woefully inadequate for addressing structural and interpersonal racism in the day‐to‐day experiences of Black birthing people and in their encounters with the health care system . Health care services that are grounded in relationships that acknowledge dynamics of power and that foster mutual respect may help shift pernicious patterns of racial inequity in perinatal care and childbirth.…”
mentioning
confidence: 99%
“…[5][6][7][8] Perinatal care, as currently designed and delivered in most settings in the United States, has proven woefully inadequate for addressing structural and interpersonal racism in the day-to-day experiences of Black birthing people and in their encounters with the health care system. [8][9][10][11] Health care services that are grounded in relationships that acknowledge dynamics of power and that foster mutual respect may help shift pernicious patterns of racial inequity in perinatal care and childbirth.…”
mentioning
confidence: 99%